A student is trying to solve the set of two equations given below:Equation A: x + z = 6
Equation B: 2x + 4z = 1

Which of the following is a possible step used in eliminating the z-term?


Multiply equation B by 4.
Multiply equation A by 2.
Multiply equation A by –4.
Multiply equation B by 2.

Answers

Answer 1
Answer: Hello,
Multiply equation A by –4.
=>-4x-4z=-24
     2x+4z=1
------------------
-2x=-23
x=23/2


Answer 2
Answer:

Answer:

To eliminate the z-term, you need to multiply equation A by -4.

Step-by-step explanation:


Related Questions

Find the sum of (–4 + i) and (10 – 5i).a. –3 + 5i b. –3 - 5i c. 6 – 4i d. 6 – 6i
PLEASE ANSWER ASPAA The x-intercept of the equation 2y – x = -6 is: 3. -3. 6. None of these choices are correct.
The square root of 80 p to the 3rd
Select the proper order from least to greatest for 1/2, 5/6, 2/7, 4/2?
Write the number 28.75 to the nearest whole number

Write the number in standard notation 6.43 x 10 ^-4

Answers

The number 6.43 * 10^(-4) in standard notation is 0.000643.

In scientific notation, numbers are expressed in the form of a * 10^b, where a is a decimal number between 1 and 10 (inclusive), and b is an integer that represents the power of 10 by which a is multiplied.

For the number 6.43 * 10^(-4):

The decimal number a is 6.43. It is greater than or equal to 1 but less than 10, as it falls within the range [1, 10).

In this case, a is 6.43.

The exponent b is -4.

This indicates that the decimal number a is multiplied by 10 raised to the power of -4.

To calculate the value of the number in standardnotation, we perform the multiplication:

6.43 * 10^(-4) = 6.43 * 0.0001

Now, we can simplify the multiplication:

6.43 × 0.0001 = 0.000643

Hence, the number 6.43 * 10^(-4) in standard notation is 0.000643.

To learn more on Number system click:

brainly.com/question/1763119

#SPJ5

Find the length of EG:
G
C
E
B.

Answers

Answer:

16

Step-by-step explanation:

17. Find all the real fourth roots of 0.0001.

Answers


3. 0.1778, -0.1778 Are you sure that you don't mean the fourth root of 0.0001?That would be 0.1, -0.1 

The value of a boat, in dollars, x years after its purchase is represented by the function.f(x)=10,000(0.73)^x



What is the average decrease in value per year between years 1 and 2?

Answers

Given the function f(x) = 10000(0.73)^x

Where y is The value of a boat, in dollars, x years after its purchase 
at x = 1
f(1) = 10000(0.73)^1
f(1) = $7300  
at x = 2
f(2) = 10000(0.73)^2
f(2) = $ 5329  
so the decrease
D = $7300 - $ 5329
D = $ 1971

 

Answer:

The correct answer is $1971.

I just took the test and got it right.

Provide the reasons for the fol owing proof Given: JK ≅ KL, NK ≅ KM
Prove ΔNKJ ≅ ΔMLK

Statements Reasons

1. JK≅KL,NK≅KM 1. Given

2.
3. ΔNKJ ≅ ΔMLK 3.________


ANSWER CHOICES

a. reflexive property of ≅ ; SAS
b. reflexive property of ≅ ; ASA
c. vertical angles are congruent; ASA
d. vertical angles are congruent; SAS

Answers

Answer:

Option d is correct.

Vertical angles are congruent;

SAS

Step-by-step explanation:

Given:JK \cong KL , NK \cong KM

In ΔNKJ and  ΔMLK

JK \cong KL and      [Side]                 {Given}

NK \cong KM      

Vertical angles states that the two lines intersect to make an X, angles on opposite sides of the X are called vertical angles.

i.e \angle NKJ and \angle MKL are vertical angles.

Also, vertical angles are congruent.

\angle NKJ \cong \angle MKL  [Angle]      [Vertical angles are congruent]

SAS(Side-Angle-Side) postulate states that if two sides and the included angle of one triangle are congruent to two sides and the included angle of another triangle, then the two triangles are congruent.

then, by SAS postulates;

\triangle NKJ \cong \triangle MLK          Hence proved!

Therefore:

Statement                                                                      Reason

1.  JK \cong KL, NK \cong KM           Given

2.  \angle NKJ \cong \angle MKL                 Vertical angles are congruent

3. \triangle NKJ \cong \triangle MLK             SAS

Answer would be D, as the triangles are congruent due to being verticle angles (literally, you can just see theyre the same). Its SAS because you have 2 exact same sides, plus an exact same angle

Solve these systems of equations Using the elimination method.a). 3x + y = 13 b) 6x - y = 14
x - 5y = 15 2x + y = 12





c) 3x - 4y = 22
2x + 5y = 7

Answers

a. 3x + y = 13 → 15x + 5y = 65
    x -  5y = 15 →     x -  5y = 15
                                     16x = 80
                                      16     16
                                        x = 5
                                 x - 5y = 15
                                 5 - 5y = 15
                               - 5          - 5
                                     -5y = 10
                                      -5     -5
                                        y = -2
                                 (x, y) = (5, -2)

b.    6x - y = 14
      2x + y = 12
            8x = 26
             8      8
              x = 3¹/₄
       6x - y = 14
6(3¹/₄) - y = 14
   19¹/₂ - y = 14
 - 19¹/₂       - 19¹/₂
             -y = -5¹/₂
             -1      -1
               y = 5¹/₂
        (x, y) = (3¹/₄, 5¹/₂)

c. 3x -  4y = 22 → 15x - 20y = 110
    2x + 5y =   7 →  8x + 20y =   28
                                        23x = 138
                                         23       23
                                            x = 6
                                   3x - 4y = 22
                                3(6) - 4y = 22
                                   18 - 4y = 22
                                 - 18         - 18
                                         -4y = 4
                                          -4    -4
                                            y = -1
                                     (x, y) = (6, -1)
a). 3x + y = 13 
x - 5y = 15 
multiplier equation 1 by 5
15x+5y=65
DSA
15x+5y=65
x - 5y = 15 
remaining
16x=80
x=5
5-5y=15
-5y=15-5
-5y=10
y=
10 ÷ -5
y=-2
x,y
5,-2